The Politics of Difference and Inclusiveness within the Canadian Labour Movement - Warskelt, Rosemary (Economic and Industrial Democracy, 1996)
Times have changed for Canadian unions in a number of important ways. Economic restructuring has wrought fundamental transformations in workplaces, labour processes and hence in unions themselves. The union movement is now largely made up of Canadian unions rather than American/international unions. The feminization of the labour market over the last 20 years has also changed the membership of unions and their organizations. Yet there are important ways in which the union movement as a whole has not responded to these challenges. The problems derive in part from the fragmented structure of the Canadian labour movement. Yet the strategies adopted by liberal and union feminists, with their emphasis on legislative solutions, have also contributed to the marginalization of women from the unions' main business, collective bargaining.